1996
DOI: 10.1029/95ja02722
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint analysis of a bursty bulk flow event on April 11, 1985

Abstract: In an attempt to place short-lived, high-speed magnetotail flows termed bursty bulk flow events (BBFs) in the context of substorm phenomenology we analyze one such event that took place on April 11, 1985, using data from several spacecraft and many ground stations. The substorm onset, which took place at 0127 UT, had a meridian 2 hours of local time east of AMPTE/IRM. The satellite did not detect high-speed flows at that time. A high-latitude (--•70 ø corrected geomagnetic) substorm intensification took place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 194 publications
(164 citation statements)
references
References 69 publications
8
156
0
Order By: Relevance
“…The plasma sheet is quite active in a manner that is reminiscent of the BBF and fast flow phenomena discussed by Baumjohann et al [ 1990], Angelopoulos et al [ 1992Angelopoulos et al [ , 1994Angelopoulos et al [ , 1996, and Fairfield et al [1998,1999]. Steady magnetospheric convection, as the name implies, has been explained in terms of convection in the plasma sheet [Hau et al, 1989], but to our knowledge, the deep minimum in the tail magnetic field required by this explanation has not been found.…”
Section: Unloading Event Figure 3 Gives Another Representation Of Onmentioning
confidence: 90%
See 1 more Smart Citation
“…The plasma sheet is quite active in a manner that is reminiscent of the BBF and fast flow phenomena discussed by Baumjohann et al [ 1990], Angelopoulos et al [ 1992Angelopoulos et al [ , 1994Angelopoulos et al [ , 1996, and Fairfield et al [1998,1999]. Steady magnetospheric convection, as the name implies, has been explained in terms of convection in the plasma sheet [Hau et al, 1989], but to our knowledge, the deep minimum in the tail magnetic field required by this explanation has not been found.…”
Section: Unloading Event Figure 3 Gives Another Representation Of Onmentioning
confidence: 90%
“…In the NENL vicinity [Nagai et al, 1998] the plasma sheet is dominated by strong turbulence during all phases of the substorm cycle [Borovsky et al, 1997]. Reconnection occurs at spatiotemporally localized sites during all phases of the substorm cycle [Baumjohann et al, 1990;Angelopoulos et al, 1992Angelopoulos et al, , 1994Angelopoulos et al, , 1996Fairfield et al, 1998Fairfield et al, , 1999Lyons et al, 1999], including the substorm expansion phase [Nagai et al, 1998]. Plasmoids are released at these localized reconnection sites during all phases of the substorm cycle; plasmoid release is not restricted to the substorm expansion phase [Ieda et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Angelopoulos et al [1994] determined in a statistical study the BBF-associated transport of magnetic flux by calculating the quantity E y = Àv x B z . The mean magnetic flux for earthward propagating BBFs was found therein to be 2.6 Â 10 6 Wb/R E and 4 Â 10 7 Wb/R E for a single event on 11 April 1985 [Angelopoulos et al, 1996]. These values correspond only to a fraction of the total magnetic flux transport.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Here we only mention briefly two competing models. Earlier studies have suggested that bursty bulk flows and ballooning instability could provide the disturbance which lead to vortex formation [e.g., Angelopoulos et al, 1996;Voronkov et al, 1997;Shiokawa et al, 1997;Birn et al, 2004]. The vortex cartoon shown in Figure 10 has been proposed for bubbles in the magnetotail [Birn et al, 2004].…”
Section: Summary and Discussionmentioning
confidence: 99%